Uit: album 26, p. 16: huldiging van Albarda in Kunsten en Wetenschappen vanwege diens 25-jarig Kamerlidmaatschap door de AJC
Uit: album 26, p. 16: huldiging van Albarda in Kunsten en Wetenschappen vanwege diens 25-jarig Kamerlidmaatschap door de AJC.